Jenis Kemasan dan Lama Penyimpanan terhadap Karakteristik Sambal â€œMarotoâ€ Khas Sumba Barat Daya - Roseline Adiyaksa Maghu; I Putu Candra; I Gede Pasek Mangku (Fakultas Pertanian, Universitas Warmadewa, 2019)
Southwest Sumba is one of the regencies in East Nusa Tenggara which has a special sambal which is very popular because of its interesting taste and aroma, the